Year-round-based optimization of high‐low control in the regenerative indirect evaporative cooler (RIEC). (26th November 2019) - Yan, Huaxia; Chen, Yi; Zhang, Weilong
Abstract : The performance of the regenerative indirect evaporative cooler (RIEC) highly depends on ambient temperature and humidity. To maintain indoor thermal comfort, proper control strategy is essential. Previous research indicates that high–low (H-L) control by using multispeed technology is superior to the conventional on–off control in terms of energy consumption and thermal comfort. Under H-L control, a fan switches between a high speed and a low speed. The high speed is determined by the peak load. However, the selection of low speed involves a great sense of subjectivity. Therefore, the influence of low speed on system performance is comprehensively investigated and an optimal low speed to high speed ratio (L/H) is determined. An optimization method is proposed by considering annual energy consumption, predicted mean vote, temperature fluctuation, and switch frequency of fan speed. Case studies have been conducted in some typical hot and arid regions. The results show that better thermal comfort can be provided under lower L/H from the aspects of high control precision and low temperature fluctuation. The switch frequency of fan speed and the annual energy consumption first decrease and then increase with the increment of L/H. The optimal L/H is between 0.2 to 0.3 from a year-round perspective and with comprehensive consideration.